The Explanation of Life Experience Reflection as Ideas of Artistic Research - Hery Budiawan; Yusup Sigit Martyastiadi (IJCAS (International Journal of Creative and Arts Studies), 2020)
In Indonesia's artistic research, especially for art creation research, many art creative ideas are born from personal experience; however, the artists' subjectivity often constrains them in expressing these experiences. This condition triggers a lack of scientific publications relating to explaining life experiences that underlie creating artwork. This article describes the process of explaining the life experience reflection into the idea of creating artworks. This method is needed to explain emotional triggers into objective knowledge as a scientific research manuscript. This artistic research employs a practice-led research approach. The analysis and discussion are carried out through reflection between ideas of creation, artworks, reviews of existing artworks, and related literature. Researchers convince that the practice-led research methodology is very strategic to boost the quality of writing artistic articles, dissemination, and presentation of arts. Also, this methodology is expected to overcome the gap between art creation and scientific publications. This study offers steps to uncover subjective experiences into objective research. This artistic research can be used to conquer the subjectivity in art creation and the imbalance between scientific publications and the writing of art creation practices. Penjelasan Refleksi Pengalaman Hidup sebagai Gagasan Penelitian Artistik ABSTRAK Dalam penelitian artistik di Indonesia, khususnya untuk penelitian penciptaan seni; banyak ide penciptaan seni yang lahir dari pengalaman pribadi, namun mereka sering terkendala oleh subjektivitas seniman dalam mengekspresikan pengalaman ini. Hal ini memicu kurangnya publikasi ilmiah yang berkaitan dengan penjelasan pengalaman hidup yang mendasari gagasan penciptaan karya seni. Artikel ini menjabarkan proses penjelasan refleksi pengalaman hidup ke dalam gagasan penciptaan karya seni. Metode ini diperlukan untuk menjelaskan hal yang subjektif ke dalam pengetahuan yang lebih objektif sebagai naskah penelitian ilmiah. Penelitian artistik ini menggunakan pendekatan penelitian yang didorong oleh praktik (PLR). Analisis dan diskusi dilakukan melalui refleksi antara ide-ide penciptaan, karya seni, ulasan karya seni yang ada, dan literatur terkait. Para peneliti yakin bahwa metodologi penelitian yang didorong oleh praktik sangat tepat guna dalam meningkatkan kualitas penulisan artikel, publikasi dan penyajian seni. Selain itu, metodologi ini diharapkan dapat mengatasi kesenjangan antara praktik penciptaan seni dan publikasi ilmiah. Penelitian ini menawarkan langkah-langkah untuk mengungkap pengalaman subjektif ke dalam penelitian ilmiah yang objektif. Penelitian artistik ini dapat digunakan untuk menjembatani antara subjektivitas dalam penciptaan seni dan ketidakseimbangan antara publikasi ilmiah dan penulisan praktik penciptaan seni.